甘油二酯的降血脂及控制体质量作用机制研究进展Research progress on the mechanism of diacylglycerol on reducing blood lipid and controlling body weight - 施丽娜1，王亚群2，王明星2，王月华2，程芳园2，金俊1，金青哲1，吴港城1，王兴国1SHI Lina1，WANG Yaqun2，WANG Mingxing2，WANG Yuehua2，CHENG Fangyuan2， JIN Jun1，JIN Qingzhe1，WU Gangcheng1，WANG Xingguo1 (Zhongguo youzhi)
甘油二酯（DAG）是甘油三酯中一个脂肪酸被羟基取代形成的酯，是膳食油脂中的天然成分之一。旨在为DAG油作为降脂减重功能性油脂的应用提供理论参考，介绍了DAG的降血脂及控制体质量功效，并综述了其作用机制。DAG因其自身的特异性结构而具有与TAG不同的消化特性，且DAG可以上调小肠中脂肪氧化、产热基因的表达，上调肝脏中β-氧化相关基因表达，抑制脂质转运和增强血浆脂质清除作用。综上，基于DAG本身结构的特异性消化代谢途径以及DAG摄入后对脂质代谢相关基因的调控，DAG可有效降低餐后血脂水平并减少体内脂肪积累，达到控制体质量的效果，改善或预防肥胖的发生。Diacylglycerol (DAG) is an ester formed by the substitution of a fatty acid by a hydroxyl group in triglycerides, and it is one of the natural components of dietary fats and oils. In order to provide a theoretical reference for the application of DAG oil as a functional blood lipid-lowering and weight-reducing oil, the blood lipid reduction and body weight control efficacy of DAG were introduced, and the mechanism of action was reviewed. DAG has different digestive properties from TAG due to its own specific structure, and DAG can up-regulate the expression of fat oxidation and thermogenesis genes in the small intestine, the expression of genes related to β-oxidation in the liver, inhibit lipid transport and enhance plasma lipid clearance. In conclusion, based on the specific digestive and metabolic pathways of DAG and the regulation of lipid metabolism-related genes after DAG intake, DAG can effectively reduce the postprandial lipid level and the accumulation of body fat to achieve the effect of controlling body weight and improving or preventing the occurrence of obesity.